Partonun di Pematang Siantar (Sebuah Catatan Transformasi Gagasan Pembuatan Ulos) - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2007)
AbstractUlos is a traditional clothes made by Batak People. The Perception for partonun (people whom made ulos) is about how ways they make it. This article want to explain the comparison their main idea from the past until now, using ethnoarchaeology approach.